Morphometric Analysis Of Coronoid Process Of Mandible By CT In The Malaysian Population: An Important Step For Determination Of Sex - Aspalilah Alias; Abdel Nasser Mohamad Ibrahim; Siti Noorain Abu Bakar; Mohamed Swarhib Shafie; Faridah Mohd Nor; Faezah Rokhani (NorCal Open Access Publications, 2024)
Introduction: Sex determination is vital for developing biolog-ical profile in skeletonized remains. Estimation of age, ancestry, and stature are dependent on sex determination. Various parts of cranial and postcranial elements were studied for sex dimor-phism in the literature. It is shown that the skeletal morpholo-gy in different sex was more pronounced in the adults than in the pre-pubertal period. Objective: The aim of this study was to determine sex in Malaysian adults by morphometric analysis of CT-scanned mandibles. Materials and Methods: The study was performed on 447 slices of scanned mandibles (894 differ-ent sides) in 244 males and 203 females. They comprised Malays (150), Chinese (137) and Indian (160) subjects within 18 to 87 years of age. Results: About ten parameters namely, perimeter and area of a triangle (formed by anterior ramus, coronion and mandibular notch) on the right and left side of mandible, and distances between anterior ramus and coronion, and between anterior ramus and mandibular notch and between coronion and mandibular notch (right and left sides of mandible) were an-alysed. By independent t-test, males were greater than females in all ten parameters (p<0.01). Paired t-test between different sides of the coronoid process showed greater values on the right than left (p<0.01). The discriminant function showed correct classification rate for 70% of cases, with identification accuracy of 75.8% for male and 63.1% for female. Conclusion: In brief, mandible is a sexually dimorphic bone useful for identification in forensic scenario. This is a pioneer study of the mandible in the Malaysians, which should be validated in future research.